Nuevos esgrafiados procedentes de Contrebia Belaisca (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
We present the news and the first transcription proposal of a graffito written in Palaeohispanic script on the jar 09.4.4181 found in the archaeological site of Contrebia Belaisca (Botorrita, Zaragoza).
Keywords: Palaeohispanic Epigraphy; Graffiti; Contrebia Belaisca